2022
DOI: 10.1039/d2sm00598k
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell microgels synthesized in continuous flow: deep insight into shell growth using temperature-dependent FTIR

Abstract: While core-shell microgels have been intensively studied in their fully synthesized state, the formation mechanism of the shell has not been completely understood. Such insight is decisive for a customization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It has to be kept in mind that the core in the core‐shell microgels presumably has smaller dimensions, as the shell is synthesized onto a collapsed version of the core. [ 50 ] Because of this, no quantitative statements regarding the size of the shell can be made.…”
Section: Resultsmentioning
confidence: 99%
“…It has to be kept in mind that the core in the core‐shell microgels presumably has smaller dimensions, as the shell is synthesized onto a collapsed version of the core. [ 50 ] Because of this, no quantitative statements regarding the size of the shell can be made.…”
Section: Resultsmentioning
confidence: 99%
“…The reactor was heated to 80 °C (Haake DC10, Thermo Fisher Scientific, Waltham, MA). In earlier works, we have shown that the desired temperature is reached after a finite heat-up time of 23 s, while the cooled stock solution remained stable over several hours . The microgels investigated by photon correlation spectroscopy were synthesized without the SAXS setup as sampling in the sample environment was not possible.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier works, we have shown that the desired temperature is reached after a finite heat-up time of 23 s, while the cooled stock solution remained stable over several hours. 33 The microgels investigated by photon correlation spectroscopy were synthesized without the SAXS setup as sampling in the sample environment was not possible. These microgels were directly quenched in liquid nitrogen after leaving the reactor.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation